**Hey there! :)**

If you switch the equation around, it becomes: 14 + x = 4

x = -10 because: **-10** + 14 = 4

**x = -10**

Hope this helps** :)**

**Answer:**

Center at (4, 7) and radius is √49, or 7

**Step-by-step explanation:**

Didn't you mean (x-4)² + (y-7) ² = 49?

Comparing (x-4)² + (y-7) ² = 49

to (x - h)^2 + (y - k)^2 = r^2, we see that the center is at (h, k) => **(4, 7) and that the radius is √49, or 7**.

1. x - 5 = 7

+5 +5

x = 12

2. -5 + x = 7

+5 +5

x = 7

3. -7x = 28

/-7. /-7

x = 4

not sure on the last one

**Answer:**

d

**Step-by-step explanation:**

plan 2 grows exponentially so it grows at a faster rate than plan 1, even though plan 1 starts with 100 members